Sex-Based Differences in pH Parameters and Esophageal Impedance of Patients With Gastroesophageal Reflux Disease - Ye, Bixing; Wang, Yanjuan; Lin, Lin; Jiang, Liuqin; Wang, Meifeng (Frontiers in Medicine, 2021)
Background/Aims The incidence of reflux esophagitis (RE) has a striking predominance in males. Conversely, nonerosive reflux disease (NERD) is more common in females. This imbalance of gastroesophageal reflux disease (GERD) implies sex-related differences in its pathogenesis. However, limited studies have analyzed the sex-based differences in pH parameters and esophageal impedance of GERD patients. Methods This study evaluated sex-based pathogenesis differences by comparing reflux episodes, mean nocturnal baseline impedance (MNBI) values, and post-reflux swallow-induced peristaltic wave (PSPW) index values of males with GERD and females with GERD using 24-hour multichannel intraluminal impedance and pH monitoring. Results We analyzed 181 patients (102 males and 79 females) with GERD. Males had significantly longer acid exposure times, higher DeMeester scores, and more acid reflux episodes than females (P < 0.05). Females had more instances of weakly acidic reflux than males (P < 0.01). The PSPW index values of males and females were similar (P > 0.05). Compared with females, males had lower MNBI values for the mid and distal esophagus (P < 0.05). However, with increasing age, the MNBI values of females decreased more rapidly than those of males. MNBI values of elderly patients of both sexes older than 60 years were similar. Conclusions Acid reflux is more likely to occur in males; however, females tend to have more instances of weakly acid reflux. The integrity of the esophageal mucosa is more fragile in males than in females; however, the esophageal mucosal barrier attenuates more rapidly with increasing age in females than in males.